Strategies to improve fertility in postpartum multiparous Bos indicus cows submitted to a fixed-time insemination protocol with gonadotropin-releasing hormone and prostaglandin F-2 alpha - Sa Filho, O. G. [UNESP]; Vilela, E. R. [UNESP]; Geary, T. W.; Vasconcelos, José Luiz Moraes [UNESP] (Amer Soc Animal Science, 2009)
In Exp. 1, we evaluated the effects of 2 lengths of progesterone exposure [CIDR (controlled intravaginal drug release); 7 vs. 14 d] before a modified CO-Synch protocol [50.0-mu g injection of GnRH 6.5 d before a 25.0-mg injection of PGF(2 alpha) followed by another injection of GnRH and fixed-time AI (TAI) 2 d after PGF(2 alpha)], with or without temporary weaning (TW) before GnRH treatments, on fertility of suckled multiparous Bos indicus cows (n = 283) and on calf performance. Timed AI pregnancy rates for cows receiving 7 d CIDR + TW, 7 d CIDR, 14 d CIDR + TW, and 14 d CIDR were 53, 47, 46, and 41%, respectively (P > 0.10). Calves submitted to two 48-h TW 6 d apart had decreased mean BW at 240 d (187.9 +/- 2.7 vs. 195.5 +/- 2.7 kg; P < 0.05), but BW at 420 d was not affected by TW (240.1 +/- 5.1 kg). In Exp. 2, we evaluated the effect of no treatment and treatment with or without a CIDR insert between GnRH and PGF(2 alpha) treatments of a modified CO-Synch protocol on pregnancy rate to TAI, and throughout a 90-d breeding season in suckled multiparous Bos indicus cows (n = 453). The inclusion of a CIDR between first GnRH and PGF(2 alpha) treatments of a modified CO-Synch protocol did not improve pregnancy rate (29 and 33% for cows receiving CO-Synch + CIDR and CO-Synch protocol, respectively), and cycling cows had poorer TAI pregnancy rates than anestrous cows treated with either synchronization protocol (21.7 vs. 40.7%; P < 0.05). However, regardless of treatment with CIDR, cows submitted to TAI protocol had greater (P < 0.05) pregnancy rates at 30 (54.8 vs. 11.2%), 60 (72.1 vs. 38.8%), and 90 d (82.0 vs. 57.9%) of breeding season than untreated cows.
Keywords: anestrous; Bos indicus; gonadotropin-releasing hormone; progesterone-releasing intravaginal insert; prostaglandin F-2 alpha; timed artificial insemination